2019
DOI: 10.3390/jcm8030294
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Exercise on Cognitive Performance in Individuals with Known Vascular Disease: A Systematic Review

Abstract: Patients with known vascular disease are at increased risk for cognitive impairments. Exercise has been shown to improve cognition in healthy elderly populations and those with mild cognitive impairments. We explored the literature to understand exercise as a modality to improve cognition in those with vascular disease, focusing on dose-responses. A systematic review was conducted through 2017 using Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane, Ovid Embase, and Ovid MEDLINE datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 72 publications
0
15
0
1
Order By: Relevance
“… 16 Furthermore, a recent systematic review found that exercise affected cognitive performance positively in those with known vascular disease. 92 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Furthermore, a recent systematic review found that exercise affected cognitive performance positively in those with known vascular disease. 92 …”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, a recent systematic review found that exercise affected cognitive performance positively in those with known vascular disease. 92 There are several limitations to the MedEx-UK study which warrant discussion. First, consistent with most other RCTs in this area, 93 it is not possible to blind participants to the intervention.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Indeed, in patients with known cardiovascular diseases such as heart failure and stroke, the degree of improvement in cognitive performance was related to exercise duration, frequency, and intensity. Further, combined interventions might be more efficient than endurance and resistance training alone [93].…”
Section: Exercise Characteristics and Improvement In Cognitive Funmentioning
confidence: 99%
“…Persistent physical activity and exercise is important for maintaining motor function across all life stages after stroke (5). Regular physical activity and exercise not only has positive effects on stroke survivors' physical improvement but also has bene ts for cognitive function rehabilitation (6), psychological domains, and quality of life (7). Systematic reviews have con rmed the bene ts of physical activity and exercise in stroke survivors (8,9).…”
Section: Introductionmentioning
confidence: 99%